FARMING EFFICIENCY AND AGRICULTURAL EXTENSION PERFORMANCE IN CENTRAL JAVA - Sucihatiningsih Dian Wisika Prajanti (Universitas Islam Indonesia, 2012)
The study aims to analyze the level of agricultural sector efficiency and agricultural extension performance in Central Java. A stochastic production function is used to estimate the efficiency. Meanwhile, descriptive statistics was employed to assess the performance of agricultural extension. The result reveals that agricultural sectors; corn, rice, and vegetable, are considered to be less efficient. However, there is an opportunity to optimize the agricultural products by using production factors based only on the needs. Moreover, it is found that the respondents' perception of the agricultural extension performance is less optimum and the number of extension is not yet ideal. Keywords: Efficiency, stochastic frontier, performance, agricultural extension JEL Classification Numbers: C61, Q16.AbstrakPenelitian ini bertujuan untuk menganalisis tingkat efisiensi sektor pertanian dan kinerja penyuluh pertanian di Propinsi Jawa Tengah. Model fungsi produksi stokastik disusun untuk memperkirakan tingkat efisiensi, dan statistik deskriptif digunakan untuk menaksir kinerja penyuluhan pertanian. Hasil penelitian menunjukkan bahwa pertanian jagung, padi, dan sayur belum efisien. Masih terdapat kesempatan untuk mengoptimalkan produksi pertanian melalui penyuluhan untuk menggunakan faktor produksi berdasarkan kebutuhan. Persepsi responden terhadap kinerja penyuluh pertanian menunjukkan bahwa mereka belum optimal dan jumlahnya belum ideal.Kata kunci: Efisiensi, stochastic frontier, penyuluhan pertanianJEL Classification Numbers: C61, Q16